Semiconductor quantum dots as an ideal source of polarization-entangled photon pairs on-demand: a review. (6th June 2018) - Huber, Daniel; Reindl, Marcus; Aberl, Johannes; Rastelli, Armando; Trotta, Rinaldo
Abstract: More than 80 years have passed since the first publication on entangled quantum states. Over this period, the concept of spookily interacting quantum states became an emerging field of science. After various experiments proving the existence of such non-classical states, visionary ideas were put forward to exploit entanglement in quantum information science and technology. These novel concepts have not yet come out of the experimental stage, mostly because of the lack of suitable, deterministic sources of entangled quantum states. Among many systems under investigation, semiconductor quantum dots are particularly appealing emitters of on-demand, single polarization-entangled photon pairs. While it was originally believed that quantum dots must exhibit a limited degree of entanglement related to decoherence effects typical of the solid-state, recent studies have invalidated this preconception. We review the relevant experiments which have led to these important discoveries and discuss the remaining challenges for the anticipated quantum technologies.